Stratigraphic calibration of Oligocene-Miocene organic-walled dinoflagellate cysts from offshore Wilkes Land, East Antarctica, and a zonation proposal - Bijl, Peter K.; Pross, Jörg; Sangiorgi, Francesca (Journal of micropalaeontology, 2018)
There is growing interest in the scientific community in reconstructing the paleoceanography of the Southern Ocean during the Oligocene-Miocene because these time intervals experienced atmospheric CO2 concentrations with relevance to our future. However, it has remained notoriously difficult to put the sedimentary archives used in these efforts into a temporal framework. This is at least partially due to the fact that the bio-events recorded in organic-walled dinoflagellate cysts (dinocysts), which often represent the only microfossil group preserved, have not yet been calibrated to the international timescale. Here we present dinocyst ranges from Oligocene-Miocene sediments drilled offshore the Wilkes Land continental margin, East Antarctica (Integrated Ocean Drilling Program (IODP) Hole U1356A). In addition, we apply statistical means to test a priori assumptions about whether the recorded taxa were deposited in situ or were reworked from older strata. Moreover, we describe two new dinocyst species, Selenopemphix brinkhuisii sp. nov. and Lejeunecysta adeliensis sp. nov., which are identified as important markers for regional stratigraphic analysis. Finally, we calibrate all identified dinocyst events to the international timescale using independent age control from calcareous nanoplankton and magnetostratigraphy from IODP Hole U1356A, and we propose a provisional dinoflagellate cyst zonation scheme for the Oligocene-Miocene of the Southern Ocean.
Gesehen am 14.02.2018